2017
DOI: 10.1186/s40478-017-0411-2
|View full text |Cite
|
Sign up to set email alerts
|

Locus coeruleus cellular and molecular pathology during the progression of Alzheimer’s disease

Abstract: A major feature of Alzheimer’s disease (AD) is the loss of noradrenergic locus coeruleus (LC) projection neurons that mediate attention, memory, and arousal. However, the extent to which the LC projection system degenerates during the initial stages of AD is still under investigation. To address this question, we performed tyrosine hydroxylase (TH) immunohistochemistry and unbiased stereology of noradrenergic LC neurons in tissue harvested postmortem from subjects who died with a clinical diagnosis of no cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
239
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(257 citation statements)
references
References 124 publications
(189 reference statements)
16
239
2
Order By: Relevance
“…In a recent study, patients with amnestic mild cognitive impairment exhibited a 30% loss of neuronal cells in the LC [75]. Those patients may have a prodromal stage of Alzheimer's disease.…”
Section: Concluding Remarks and Implicationsmentioning
confidence: 99%
“…In a recent study, patients with amnestic mild cognitive impairment exhibited a 30% loss of neuronal cells in the LC [75]. Those patients may have a prodromal stage of Alzheimer's disease.…”
Section: Concluding Remarks and Implicationsmentioning
confidence: 99%
“…Degeneration of the noradrenergic brainstem locus coeruleus (LC) is an early and ubiquitous feature of AD that correlates well with many of its other elements, such as ␤-amyloid (A␤) plaques, tau neurofibrillary tangles, and cognitive impairment (Iversen et al, 1983;Mann, 1983;Bondareff et al, 1987;Chan-Palay and Asan, 1989;Haglund et al, 2006;Grudzien et al, 2007). Norepinephrine (NE) is important for many AD-relevant behaviors and cognitive functions (e.g., arousal, attention, affective behaviors, learning, and memory) in addition to having anti-inflammatory and neuroprotective properties (Szabadi, 2013;Feinstein et al, 2016;Mather and Harley, 2016). Thus, as the sole source of NE to critical AD-associated brain regions, such as the hippocampus and frontal cortex, damage to the LC likely contributes to disease progression and severity (Mann, 1983;Zweig et al, 1989;Jalbert et al, 2008;Gannon et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Norepinephrine (NE) is important for many AD-relevant behaviors and cognitive functions (e.g., arousal, attention, affective behaviors, learning, and memory) in addition to having anti-inflammatory and neuroprotective properties (Szabadi, 2013;Feinstein et al, 2016;Mather and Harley, 2016). Thus, as the sole source of NE to critical AD-associated brain regions, such as the hippocampus and frontal cortex, damage to the LC likely contributes to disease progression and severity (Mann, 1983;Zweig et al, 1989;Jalbert et al, 2008;Gannon et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The LC neurons degenerate in many neurological disorders. For example, abnormal pre-tangle tau protein is detected in the LC in Alzheimer’s disease from the earliest stages (Braak et al, 2011, Grudzien et al, 2007, Kelly et al, 2017), and severe cell loss is observed in Alzheimer’s disease, Parkinson’s disease and Progressive Supranuclear Palsy (Theofilas et al, 2017, Surmeier et al, 2017, Kaalund et al, 2020). Dysregulation of the LC noradrenergic system has been associated with clinical symptoms and cognitive impairments in neurodegenerative disorders (Weinshenker, 2008, Kehagia et al, 2010, Passamonti et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%